Phenotypic plasticity in adults of Anticarsia gemmatalis exposed to sub-doses of Bt-based bioinsecticide - Fernandes,F. O. (2024)
Abstract Anticarsia gemmatalis Hünber, 1818 is one of the main defoliating species in the soybean crop. Bacillus thuringiensis Berliner, 1915, is a bacterium used in the biological control of this pest species. Resistant populations and their sublethal effects caused by the use of the bacteria have already been reported; however, there are no studies on phenotypic plasticity in adulthood exposed to Bt-based bioinsecticide sub-doses. This study aimed to evaluate the morphometry of A. gemmatalis adults under laboratory conditions submitted to the Bt-based bioinsecticide Dipel® over the three generations. The body segments mensuread were width, length, and area of the anterior and posterior wings, the weight of the integument, chest, abdomen, wings, and the whole adult of males and females. Among the treatments, LC5 in the first generation and LC10 in the second generation were those with lower thresholds in relation to the weight of the chest and abdomen, considering the proportions of the body smaller than the females. The female’s weight adulthood was reduced by 10% about males, and, only in the first generation. Males have larger body size and more pronounced phenotypic plasticity than females. Here, we demonstrate the first study assessing the phenotypic plasticity of A. gemmatalis adults.